Loss of expression and function of Gβγ by GNB1 encephalopathy-associated L95P mutation of the Gβ1 subunit - Reddy, Haritha P.; Keren-Raifman, Tal; Tabak, Galit; Dascal, Nathan; Yakubovich, Daniel (Frontiers in Pharmacology, 2025)
BackgroundG-proteins areindispensable regulators of cellular signaling, with G-protein-gated inwardly rectifying potassium channels (GIRK) as key effectors. GNB1 encephalopathy (GNB1E) is a congenital neurological syndrome resulting from mutations in the GNB1 gene, encoding the Gβ1 subunit of G-proteins trimer (Gαβγ). GNB1E manifests as a global developmental delay, accompanied by tonus disturbances, ataxia, and epilepsy.MethodsWe utilized the Xenopus laevis oocyte heterologous expression system to investigate the impact of the L95P mutation in Gβ1 (Gβ1-L95P) on the activation of neuronal GIRK channels GIRK2 and GIRK1/2. Mutant and wild-type (WT) Gβ1 RNAs were co-injected with RNAs encoding the Gγ2 and GIRK channel subunits. The expression levels of both Gβ1 and the channel proteins, as well as the channel activity, were systematically monitored. Additionally, rigid-body docking was used to model the GIRK1/2–Gβγ complex, evaluating L95P’s effect on channel–Gβγ interaction, Gβγ stability, and Gβγ–effector affinity.Results. Gβ1-L95P exhibited reduced protein expression compared to WT. Even after RNA adjustments to restore comparable membrane localization, the mutant failed to effectively activate GIRK2 and GIRK1/2. Structural analysis revealed that L95 was not consistent in the Gβγ–effector interface. Thermodynamic calculations suggested that the mutation primarily destabilized Gβ1 and Gβ1–effector complex.ConclusionGβ1-L95P leads to both reduced protein expression and impaired function in the GIRK–Gβγ interaction system. The later effect can be attributed to the changes associated with protein misfolding.